Lipocalin-7 is a matricellular regulator of angiogenesis. - Leslie J Brown; Mariam Alawoki; Mary E Crawford; Tiffany Reida; Allison Sears; Tory Torma; Allan R Albig (PLoS ONE)
Background Matricellular proteins are extracellular regulators of cellular adhesion, signaling and performing a variety of physiological behaviors such as proliferation, migration and differentiation. Within vascular microenvironments, matricellular proteins exert both positive and negative regulatory cues to vascular endothelium. The relative balance of these matricellular cues is believed to be critical for vascular homeostasis, angiogenesis activation or angiogenesis resolution. However, our knowledge of matricellular proteins within vascular microenvironments and the mechanisms by which these proteins impact vascular function remain largely undefined. The matricellular protein lipocalin-7 (LCN7) is found throughout vascular microenvironments, and circumstantial evidence suggests that LCN7 may be an important regulator of angiogenesis. Therefore, we hypothesized that LCN7 may be an important regulator of vascular function. Methodology and principal findings To test this hypothesis, we examined the effect of LCN7 overexpression, recombinant protein and gene knockdown in a series of in vitro and in vivo models of angiogenesis. We found that overexpression of LCN7 in MB114 and SVEC murine endothelial cell lines or administration of highly purified recombinant LCN7 protein increased endothelial cell invasion. Similarly, LCN7 increased angiogenic sprouting from quiescent endothelial cell monolayers and ex vivo aortic rings. Moreover, LCN7 increased endothelial cell sensitivity to TGF-β but did not affect sensitivity to other pro-angiogenic growth factors including bFGF and VEGF. Finally, morpholino based knockdown of LCN7 in zebrafish embryos specifically inhibited angiogenic sprouting but did not affect vasculogenesis within injected embryos. Conclusions and significance No functional analysis has previously been performed to elucidate the function of LCN7 in vascular or other cellular processes. Collectively, our results show for the first time that LCN7 is an important pro-angiogenic matricellular protein of vascular microenvironments.